Solving Short Shot Defect by Designing Air Vents in Plastic Injection Molds for Coffee Cups with Biodegradable Material - Sangkas, Teerawat; Chainawakul, Adirake; Aukaranarakul, Supachai; Kowtakul, Pitchet; Manokruang, Supasit (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research addresses issues in plastic injection molding, particularly the occurrence of short shot defects, which significantly impact the quality of the produced parts. These defects arise from several critical factors, such as the material's properties used in the injection process, the complexity of the part design, and inadequate mold design. This study proposed a solution by designing an air vent system within the plastic injection mold, specifically for manufacturing coffee cups made from biodegradable materials. In this system design, two air vents were installed in the mold: the main air vent with a depth of 0.05 mm and a width of 2 mm, and the secondary air vent with a depth of 0.1 mm and a width of 10 mm, which help to vent the air generated at the final melt point of the plastic. The relevant parameters of the injection process were set as follows: injection pressure at 54 bar, injection speed rate at 40 cm3/s, clamping force at 100 Tons, melt temperature at 200 oC, and mold temperature at 90 oC. The experimental results showed that properly and efficiently designed air vent system design in the mold can significantly reduce the occurrence of incomplete injection defects, resulting in high-quality parts and reducing production losses. Therefore, this research is an important guideline for the development and improvement of future plastic injection mold designs, focusing on air vent system in the mold to increase production efficiency.